The Franck Factory in Zagreb: Location, Origin, and Strategies for its Renovation - Vedran Ivanković (Peristil)
Franck is the oldest industrial facility in Zagreb that has been continually running at the same address since its establishment. From 1892 to the 1970s, when the factory was only able to partially realize an ambitious urban design along Lola Ribar Avenue (today’s Baron Filipović Avenue), the author offers new insights into the history of the development of production plants and other related structures. He concludes by outlining the foundations for its renovation.